Sports and health from the perspective of physical education professionals - John Koumantareas; Rogério Cruz de Oliveira (Universidade Estadual Paulista (UNESP), 2018)
Abstract Aim: The objective of the study was to understand the conceptions of sports and health of Physical Education professionals working in a sports department of a municipality located in Baixada Santista region (São Paulo, Brazil) in the context of the non-training of athletes. Method: For that, a qualitative descriptive research was carried out with nine Physical Education professional, of both genders and in any age group, distributed in two sport centers. Semi-structured interviews were conducted about sports and health. Data analysis occurred using non-a priori categories. Results: As a result, the conception of sports took place through three categories: sport as a movement; sport as a formation agent for citizenship; and sport as a competitive modality. In relation to health, three categories were also identified: health as well being; health as a quality of life; and health as body care. Conclusion: It is concluded that the diversity of conceptions found reflects the polysemy that involves sports and health, and, consequently, can result in a distinct pedagogical practice from these professionals, who, allocated in the same professional context, a sports department, can generate divergences.